2020
DOI: 10.1039/c9py01533g
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate, nitrate, sulfonate, and phosphate catalysts for living radical polymerization via oxygen–iodine halogen bonding catalysis

Abstract: Oxyanions, i.e., carboxylate, nitrate, phosphate, and sulfonate, were used for halogen-bonding-catalyzed living radial polymerization, giving low-dispersity polymethacrylates, polystyrene, and polyacrylonitrile homopolymers and block copolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 40 publications
(12 reference statements)
1
24
0
Order By: Relevance
“…The addition of a small amount of I 2 (0.0125 equiv with respect to CP−I) led to a lower Đ value of 1.26 with keeping a relatively high monomer conversion (86%) for 20 h (Table 2 (entry 2) and Figure 3 (squares)). I 2 worked as a deactivator of the propagating radical and prevented the addition of many monomers to the propagating radical in an activation–deactivation cycle, [ 48 ] enabling more uniform polymer growth (narrow molecular weight distribution). Thus, the results demonstrate an efficient catalytic activity of the generated RCOO − and successful air‐tolerant two‐step polymerizations of MMA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of a small amount of I 2 (0.0125 equiv with respect to CP−I) led to a lower Đ value of 1.26 with keeping a relatively high monomer conversion (86%) for 20 h (Table 2 (entry 2) and Figure 3 (squares)). I 2 worked as a deactivator of the propagating radical and prevented the addition of many monomers to the propagating radical in an activation–deactivation cycle, [ 48 ] enabling more uniform polymer growth (narrow molecular weight distribution). Thus, the results demonstrate an efficient catalytic activity of the generated RCOO − and successful air‐tolerant two‐step polymerizations of MMA.…”
Section: Resultsmentioning
confidence: 99%
“…[ 47 ] Recently, we studied oxyanions (carboxylate (COO – ), nitrate (NO 3 – ), phosphate (PO 4 – ), and sulfonate (SO 3 – ) anions) as the catalysts, showing that carboxylate anions are particularly efficient catalysts and amenable to a range of monomers including functional methacrylates, styrene, and acrylonitrile. [ 48 ]…”
Section: Introductionmentioning
confidence: 99%
“…Our research group found the reversible reactions using alkyl iodides, enabling the use of XB catalysis to LRP. Since our first report in 2011, we have developed several types of RCMP catalysts, including amines, 40,49 iodide anion (I − ), [50][51][52][53][54] organic superbases, 55 pseudohalide anions, 56 pyridine N-oxides, 57 and oxyanions 58 (Fig. 3).…”
Section: Polymerizations and Applicationsmentioning
confidence: 99%
“…50 The free radical nature of the propagating species was supported by a radical trap experiment in low-mass model systems. [49][50][51][52][55][56][57][58] For example (Fig. 6a), an alkyl iodide CP-I (10 mM), an I − catalyst (80 mM), and a radical trap 2,2,6,6tetramethylpiperidinyl-1-oxy (TEMPO) (20 mM) were heated in a solvent at 60°C.…”
Section: Polymerizations and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation